Suppressing interference from sidelobe coupling in phased-array acoustic Doppler velocimetry based on correlation delay optimization - Li, Ding; Cao, Zhongyi (Remote sensing letters, 2024)
Velocity information is important for describing the motion state of an object. Modern underwater navigation systems use the Doppler effect to extract the absolute velocity to the bottom or relative velocity to the water layer from the acoustic backscattering signal. Suppressing interference from sidelobe coupling is very important to improve the accuracy of phased-array acoustic Doppler Velocity Log (DVL) and to realize autonomous navigation in complex ocean environments. This paper proposes an interference suppression method based on optimizing the correlation delay of the pulse-pair algorithm to reduce the sidelobe coupling interference. The results of simulations and experiments show that the proposed method reduces the effect of sidelobe coupling on velocity measurements by 70% on average, which is expected to be useful for improving the autonomous navigation performance of unmanned vehicles in complex underwater environments.